2016
DOI: 10.1120/jacmp.v17i1.5899
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐modulated radiation therapy dose verification using fluence and portal imaging device

Abstract: Patient‐specific quality assurance for intensity‐modulated radiation therapy (IMRT) dose verification is essential. The aim of this study is to provide a new method based on the relative error distribution by comparing the fluence map from the treatment planning system (TPS) and the incident fluence deconvolved from the electronic portal imaging device (EPID) images. This method is validated for 10 head and neck IMRT cases. The fluence map of each beam was exported from the TPS and EPID images of the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…That was the reason the portal dosimetry system could detect the small magnitude of error than the other two QA devices. It was agreed with Sumida et al [8] studied whom suggested that the large target should use a finer resolution detector like portal dosimetry to compensate for the software interpolation data.…”
Section: Position Shifted Error Detection By the Quality Assurancesupporting
confidence: 76%
“…That was the reason the portal dosimetry system could detect the small magnitude of error than the other two QA devices. It was agreed with Sumida et al [8] studied whom suggested that the large target should use a finer resolution detector like portal dosimetry to compensate for the software interpolation data.…”
Section: Position Shifted Error Detection By the Quality Assurancesupporting
confidence: 76%
“…[7][8][9] Since these techniques are much more complex than conventional open-field 3DCRT (3D conformal radiotherapy), more advanced and precise quality control of treatment should be implemented. [1][2][3] In present clinical procedures, the pre-treatment dosimetry verification of IMRT plan is used at the hospital as https://doi.org/10.1016/j.rpor.2018.05.003 1507-1367/© 2018 Greater Poland Cancer Centre. Published by Elsevier Sp.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, EPID has gained new importance and usefulness in radiotherapy: it can be used not only for geometric verification of patient position or for preverification dosimetry but also as a useful tool for QA of linac: verification of output, geometry or MLCs. 3,4 There is also interest in transit dosimetry and patient dose reconstruction based on measurement fluency map collected during treatment. 2,6 It is easy to use and can be placed under treatment couch with patients lying on it.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment requires high quality assurance and quality control. Dose verification for individual patients prior to treatment is required to ensure accurate treatment ( 3 ).…”
Section: Introductionmentioning
confidence: 99%